2007
DOI: 10.1021/om0610086
|View full text |Cite
|
Sign up to set email alerts
|

Group 14 and 15 Heteroallenes ECC and ECE‘

Abstract: This review describes the synthesis, physical properties, and some aspects of the reactivity of heteroallenes, namely the heavier congeners of allenes containing one or two doubly bonded heavier elements of groups 14 (Si, Ge, Sn) and 15 (P, As, Sb). The key factor for their preparation lies in the use of synthetic methods effective under mild conditions:  i.e., in many cases, the dehalogenation at low temperature of dihaloheteropropenes by lithium derivatives. Their stabilization was successful, owing to very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 158 publications
0
27
0
1
Order By: Relevance
“…From these results, it can be concluded that a stiba-alkene resonance form is less relevant than the CAAC-stibinidene form shown in 4. [20] Note that very few stiba-alkenes are known, [21] and only the stibaenol [Mes*(CO)Sb = C(Mes*)OH] [21a] has been structurally characterized (Sb = C 2.078 (3) ), which prevents any direct comparison for the SbÀC distance.…”
Section: [18b]mentioning
confidence: 99%
“…From these results, it can be concluded that a stiba-alkene resonance form is less relevant than the CAAC-stibinidene form shown in 4. [20] Note that very few stiba-alkenes are known, [21] and only the stibaenol [Mes*(CO)Sb = C(Mes*)OH] [21a] has been structurally characterized (Sb = C 2.078 (3) ), which prevents any direct comparison for the SbÀC distance.…”
Section: [18b]mentioning
confidence: 99%
“…Abbildung 2. a) Experimentelles X-Band-EPR-Spektrum von 3 (g = 2.0025), gemessen in Benzol bei Raumtemperatur. b) Simuliertes EPR-Spektrum [19] [20] Es ist zu bemerken, dass bislang nur einige wenige Stibaalkene beschrieben worden sind [21] und dass lediglich die Struktur des Stibaenols [Mes*(CO)Sb = C(Mes*)OH] (Sb = C: 2.078 (3) ; Mes = 2,4,6-Trimethylphenyl, Mes* = 2,4,6-Tri-tert-butylphenyl) bekannt ist, [21a] was einen direkten Vergleich des Sb-C-Abstands verhindert.…”
unclassified
“…Phosphaallenes 6 a – d are characterized by typical 31 P NMR chemical shifts of 57 ppm ( 6 a ), 98 ppm ( 6 b ), 60 ppm ( 6 c ), and 94 ppm ( 6 d ),7c are however highly moisture sensitive which hampers their isolation and purification. In the absence of extensive kinetic stabilization by large substituents at phosphorus, such behavior is not uncommon 7a. Water ( 8 ) and methanol ( 9 ) addition products of 6 could however be isolated and characterized, in case of 8 b and 8 c even by single‐crystal X‐ray studies (Scheme and Supporting Information).…”
Section: Methodsmentioning
confidence: 99%